The heart of darkness : growth and form of Trypanosoma brucei in the tsetse fly. - Kumar Sharma, Reuben Sunil; Eva , Gluenz; Peacock, Lori; Gibson, Wendy; Gull, Keith; Carrington, Mark (Elsevier, 2009)
The first description of African trypanosomes was made over a century ago. The importance of the tsetse in transmission and cyclic development of trypanosomes was discovered soon afterwards, and has been the focus of numerous studies since. However, investigation of trypanosomes in tsetse flies requires high resource investment and unusual patience; hence, many facets of trypanosome biology in the tsetse remain to be characterised despite the long history of research. Here, current knowledge and questions about some of the developmental changes in trypanosomes that occur in tsetse flies are summarised, along with recent technical advances that can now be used to provide some answers.